Project Based Learning for English Teaching in Vocational High School Students: A Need Analysis - Linda Ratna Susila; Khoirul Anwar; Yudhi Arifani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Project based learning knowns as an actual implementation of project-based learning strategies is one of the learning strategies that is still rarely used, especially in the vocational high school students. The study aims to find the target and learning needs for designing PBL strategy in vocational high school. This study administers a descriptive analysis with a quantitative approach. It uses the data from questionnaire distributes to respondents in order to find out the target needs and learning needs of participants. The participant of this research are 40 students of industrial electronics engineering (TEI) of 10th grade students in the academic year of 2021/2022 at SMK Manbaul Ulum Kebomas, East Jawa, Indonesia. The study results illustrated that the implementation of project-based learning strategy in the vocational high school is one of the ways to find the way how to answer this problem. In the designing and implementing of PBL here needs to find the Need Analysis (target needs and learning needs). By finding the need analysis of designing PBL strategy in learning English it helps the teacher, and students in finding the materials, method, media, and evaluation in the teaching learning process.